Sevoflurane Induction Shortens the Onset of Vecuronium at the Corrugator Supercilii Muscles: A Randomized Comparison with Propofol Induction. (28th November 2011) - Nitahara, Keiichi; Sugi, Yasuyuki; Kusumoto, Go; Katori, Kiyoshi; Iwashita, Kohei; Higa, Kazuo
Abstract : We evaluated if induction with sevoflurane shortened the onset of vecuronium-induced neuromuscular blockade at the corrugator supercilii muscles (which have a similar time course of neuromuscular blockade with laryngeal muscles). Thirty-two patients were randomly allocated to a sevoflurane or propofol group. Anesthesia was induced with 5% sevoflurane in oxygen (sevoflurane group, n = 16 ) or with propofol 2–2.5 mg kg −1 (propofol group, n = 16 ), and vecuronium (0.1 mg kg −1 ) was given in both groups. Evoked responses to train-of-four stimuli were measured by acceleromyography at the corrugator supercilii and adductor pollicis muscles. Sevoflurane induction, as compared with propofol, significantly shortened the onset time at the corrugator supercilii muscles from 138 ± 34 s to 107 ± 28 s (P < 0.01 ). Onset time at the corrugator supercilii was significantly shorter than at the adductor pollicis for both groups (P < 0.01 ). Our results suggest that induction with sevoflurane, as compared with propofol, shortened the onset time of vecuronium at laryngeal muscles.